The Effectiveness of Audio-Visual-Based Education on Type 2 Diabetes Mellitus in Enhancing Self-Awareness Among Adolescents at Risk: A Quasi-Experimental Study - Puspasari, Susy; Hardiani, Ina (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2025)
Aims: Aims of this study to determine the effect of providing audio-visual-based type 2 diabetes mellitus education on self-awareness in adolescents at risk of type 2 diabetes mellitus. Methods: A two-group quasi-experimental design is used in quantitative research, and G-Power 3.1 is used as a selection method. The 100 students in the study were split into two groups: the intervention group and the control group. The Public Awareness of Diabetes questionnaire was used. To be eligible, people had to be in the low to moderate risk group for DM and have a gadget. The Paired Sample T-test and Wilcoxon's rank were used to analyze the data. Results: The Paired Sample T-test analysis revealed a significant difference in the intervention group following education on type 2 diabetes mellitus, with a p-value of <0.001 and a t-value of 3.744. Simultaneously, the control group employed Wilcoxon's rank, yielding a p-value of 0.079 and an r-value of 1.756. Conclusions: There was an effect of providing type 2 diabetes mellitus education on self-awareness in adolescents at risk of type 2 diabetes mellitus in the intervention group. However, there was no effect of providing type 2 diabetes mellitus education on self-awareness in adolescents at risk of type 2 diabetes mellitus in the control group. This may be because there are differences in the treatment given to the two groups.